Importance of a Resident Pharmacist in a Liver and Kidney Transplantation Unit: Pharmaceutical Interventions Performed - Souza, Thalita Rodrigues de; Lopes, Diana Maria de Almeida; Freire, Natália Martins; Salmito, Geysa Andrade; Vasconcelos, Helaine Cristina Alves de; Oliveira, Alene Barros de; Pinheiro, Alexsandra Nunes; Néri, Eugenie Desirèe Rabelo; Fernandes, Paula Frassinetti Castelo Branco Camurça; Garcia, José Huygens Parente (Brazilian Journal of Transplantation, 2010)
The role of clinical pharmacists in the patient care in hospitals has evolved over time, with emphasis on pharmaceutical care. In this scenario, the resident pharmacist has substantially contributed to liver and kidney transplant patients and to the benefits from pharmaceutical interventions that act as an effective tool to improve the quality of the hospital care. Purpose: To report pharmaceutical interventions (PI) performed by the resident pharmacist in a kidney and liver transplantation unit at a University Hospital, identifying drug related problems (DRP) along the admission period and discharge of transplanted patients. Methods: A retrospective study analyzing pharmaceutical interventions made by the resident pharmacist in kidney and liver transplanted patients from May to September, 2010. RESULTS: During the studied period, 219 patients were followed, and among them, it was detected 47 DPR (21.50%). From those patients, 51.06% (n= 24) were female. Drugs involved in the identified DPR were classified according to the Anatomical Therapeutic Chemical (ATC), with a higher prevalence of the cardiovascular and nervous systems, 43.47% and 17.39% respectively. It was identified 81 DPR, 98.75% of them were prevented through the PI, with 98.76% acceptance. Doctors were the most requested professional (97.50%), followed by nurses (2.50%). When ranked by the II Granada Consensus, needing DPR occurred in 68.80% (n= 55), safety: 28.80% (n=23), and effectiveness, 2.50% (n= 2). It was found no statistical significance in the intervention acceptance among the different DPR (p=0.873). Conclusions: Results suggest that the participation of a resident pharmacist in the medical care is useful to prevent DRP, and it is well accepted by other team members, contributing for a safe and necessary treatment for liver and kidney transplanted patients.